Ingham problem for mixed convection flow of a nanofluid over a moving vertical plate with suction and injection effects - Anuar Jamaludin,; Roslinda Nazar,; Pop, Ioan (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this study, the effects of suction and injection on the mixed convection flow of a nanofluid, over a moving permeable vertical plate were discussed. A similarity variable was used to transform the governing equations to the ordinary differential equations, which were then solved numerically using the bvp4c programme from MATLAB. Dual solutions (upper and lower branches) were found within a certain range of the mixed convection parameter in assisting and opposing flow regions. A stability analysis was implemented to confirm that the upper branch solution was stable, while the lower branch solution was unstable.